Accountability of University: Transition of Public Higher Education - Łukasz Sułkowski (Entrepreneurial Business and Economics Review, 2016)
Objective: The main goal of the article is to discuss and elaborate on the basics foundations of the concept of accountability in terms of the public universities management.